PENGARUH KUALITASPELAYANAN PAJAK, PEMAHAMAN PERATURAN PERPAJAKAN SERTA SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI YANG TERDAFTAR DI KANTOR PELAYANAN PAJAK PRATAMA KOTA BATAM - Efriyenty, Dian (Aksara Public, 2017)
This study examines the influence of the Quality of Tax Service, Understanding Tax Regulation and Tax Sanctions Against Personal Tax Payer Compliance Registered in Tax Office Pratama Batam North. This study is expected to taxpayers of individuals should be able to further improve their compliance in fulfilling their tax obligations, increasing knowledge and understanding of tax laws, so that taxpayers can be honest in reporting tax. The lack of responsiveness of the implementing institution of the tax service will have an impact on the decreasing of the public compliance to the tax service institution. In Indonesia, knowledge and understanding of taxpayers is still quite low. Understanding the taxpayer is still quite low can be seen from the existing taxpayers who do not understand the Annual Tax Return (SPT), and there are still taxpayers who make a mistake in filling the Annual Tax Return. Various kinds of tax penalties imposed to taxpayers who violate tax regulations are considered burdensome for taxpayers so many taxpayers who are then reluctant to meet their tax obligations.